Coral communities and reefs of Ballena Marine National Park, Pacific coast of Costa Rica - Juan José Alvarado; Jorge Cortés; Cindy Fernández; Jaime Nivia (Ciencias Marinas, 2005)
The coral communities and reefs at Ballena Marine National Park, on the southern Pacific coast of Costa Rica, were studied using three 10-m long transects per site, parallel to the coast, with 1-m2 quadrants. A total of 15 species of corals (11 hermatypic and 4 ahermatypic) were found, which when added to previous reports for the park makes a total of 18 species. Porites lobata showed the highest coral cover (36.5 ± 3.7%) and was the only species present at all sites. The other coral species had low coverage (<10%) and were observed in a few places. Dead coral had a cover of 1.8 ± 0.6% and the percent of bleached coral (0.7 ± 0.2%) was due to P. lobata at only one site. This park and Caño Island have the highest number of coral species (18 species) in the southern region of Costa Rica, but they differ in composition. The low diversity and low coral covr in the park is attributed to the impact of the El Niño phenomenon in recent years, to sedimentation and to the dilution of waters during the rainy season. We suggest that a long-term monitoring program of this ecosystem is needed to determine future management and conservation strategies.